GalNAc-T14 may Contribute to Production of Galactose-Deficient Immunoglobulin A1, the Main Autoantigen in IgA Nephropathy - Jemelkova, Jana; Stuchlova Horynova, Milada; Kosztyu, Petr; Zachova, Katerina; Zadrazil, Josef; Galuszkova, Dana; Takahashi, Kazuo; Novak, Jan; Raska, Milan (Kidney international reports, 2023)
INTRODUCTION: Immunoglobulin A1 (IgA1) with galactose-deficient O-glycans (Gd-IgA1) play a key role in the pathogenesis of IgA nephropathy (IgAN). Mucosal-tissue infections increase IL-6 production and, in patients with IgAN, are often associated with macroscopic hematuria. IgA1-secreting cell lines derived from the circulation of patients with IgAN, compared to those of healthy controls (HCs), produce more IgA1 that has O-glycans with terminal or sialylated N-acetylgalactosamine (GalNAc). GalNAc residues are added to IgA1 hinge region by some of the 20 GalNAc transferases, the O-glycosylation-initiating enzymes. Expression of GALNT2, encoding GalNAc-T2, the main enzyme initiating IgA1 O-glycosylation, is similar in cells derived from patients with IgAN and HCs. In this report, we extend our observations of GALNT14 overexpression in IgA1-producing cell lines from patients with IgAN. METHODS: GALNT14 expression was analyzed in peripheral blood mononuclear cells (PBMCs) from patients with IgAN and from HCs. Moreover, the effect of GALNT14 overexpression or knock-down on Gd-IgA1 production in Dakiki cells was assessed. RESULTS: GALNT14 was overexpressed in PBMCs from patients with IgAN. IL-6 increased GALNT14 expression in PBMCs from patients with IgAN and HCs. We used IgA1-producing cell line Dakiki, a previously reported model of Gd-IgA1-producing cells, and showed that overexpression of GalNAc-T14 enhanced galactose deficiency of IgA1, whereas siRNA-mediated GalNAc-T14 knock-down reduced it. GalNAc-T14 was localized in trans-Golgi network, as expected. CONCLUSIONS: Overexpression of GALNT14 due to inflammatory signals during mucosal infections may contribute to overproduction of Gd-IgA1 in patients with IgAN.
Keywords: GalNAc-T14; inflammation; IgA nephropathy; IL-6 cytokine